The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1158/1541-7786.mcr-17-0071
|View full text |Cite
|
Sign up to set email alerts
|

The Tissue-Reconstructing Ability of Colon CSCs Is Enhanced by FK506 and Suppressed by GSK3 Inhibition

Abstract: Cancer stem cells (CSC) are capable of reconstructing cancer tissues, are involved in both recurrence and metastasis, and contribute to therapeutic resistance. Therefore, elucidating the molecular mechanism in CSCs is important to successfully treat unresectable cancers. Previously, we observed that colon cancer stem-like cells can be induced from human colon cancer cell lines by retrovirally introducing OCT3/4, SOX2, and KLF4, and we have designated such cells as induced cancer stem cells (iCSC). In the curre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…The expression of a downstream target gene of ZEB1, MMP14 (a matrix metalloprotease), was also consistently suppressed in MeCP2-depleted HCT116 cells ( Figure 5C). Moreover, the expression of cancer stem cell surface antigens, including CD133 (Prominin-Like Protein 1) [21], KLF4 (Kruppel-like factor 4) [22], and Sox2 (SRY-Related HMG-Box Gene 2) [23], was reduced after MeCP2 inhibition ( Figure 5C), consistent with the aforementioned observations in the sphere formation assay. Expression of full-length MeCP2 restored ZEB1 mRNA expression in MeCP2-depleted cells ( Figure 5D left), but truncated or mutated versions of MeCP2 (Table S5, the sequence of wild type or depletion MeCP2 CDS) had no effect ( Figure 5D right).…”
Section: Zeb1 Is the Major Effector Of Mecp2supporting
confidence: 84%
“…The expression of a downstream target gene of ZEB1, MMP14 (a matrix metalloprotease), was also consistently suppressed in MeCP2-depleted HCT116 cells ( Figure 5C). Moreover, the expression of cancer stem cell surface antigens, including CD133 (Prominin-Like Protein 1) [21], KLF4 (Kruppel-like factor 4) [22], and Sox2 (SRY-Related HMG-Box Gene 2) [23], was reduced after MeCP2 inhibition ( Figure 5C), consistent with the aforementioned observations in the sphere formation assay. Expression of full-length MeCP2 restored ZEB1 mRNA expression in MeCP2-depleted cells ( Figure 5D left), but truncated or mutated versions of MeCP2 (Table S5, the sequence of wild type or depletion MeCP2 CDS) had no effect ( Figure 5D right).…”
Section: Zeb1 Is the Major Effector Of Mecp2supporting
confidence: 84%
“…It was also reported that GSK3β inhibitors suppress Bcl2-mediated and α5/β1-integrin-dependent cell survival pathways, thereby eliminating primitive leukemia progenitor/stem cells [134,137,138]. Other studies have implicated different mechanisms for the effects of GSK3β inhibition on CSCs from colorectal, head and neck and prostate cancer [42,49,76,92]. In contrast to the role of GSK3β in CSCs, previous studies have indicated that GSK3β inhibition is essential for maintaining the "stemness" phenotype in embryonic and hematopoietic SCs.…”
Section: Gsk3β Cancer Stem Cells and The "Stemness" Phenotypementioning
confidence: 99%
“…To date, the tumor-promoting functions of deregulated GSK3β have been reported in 25 cancer types from various organs and tissues across the body ( Table 1 ) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ...…”
Section: Tumor-promoting Roles Of Gsk3β In Various Cancer Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…These transcription factors are also essential for the induction of pluripotent stem cells derived from adult somatic cells (44)(45)(46)(47). The experiments presented in Fig.…”
Section: Biomarkermentioning
confidence: 99%